A critical review of airport privatisation in the Kingdom of Saudi Arabia: Case study of Medina Airport - Chaouk, Mohammed; Pagliari, Romano I.; Miyoshi, Chikage (Elsevier, 2019)
Saudi Arabia is one of the few Middle-Eastern states to have undertaken an airport privatisation programme. Medina was one of several airports that have been privatised in Saudi Arabia when it was awarded to Tibah Airports in 2012 under a Build-Transfer-Operate agreement. This paper compares the performance of Medina Airport in terms of traffic, revenues, costs and profitability with projections made during the due-diligence period prior to the airport’s privatisation. We found that the airport benefitted from favourable market conditions post-privatisation which facilitated the attainment of some important achievements with regard to route development and customer service. However, we also found that profitability was lower than forecast during the due-diligence process prior to privatisation and that this was mainly as a result of unexpected interventions by the regulator GACA. We have raised important policy implications for future privatisation transactions, the success of which is crucially dependent on the Kingdom minimising the level of regulatory risk facing potential investors. There are cultural dimensions, human resources strategies and administrative governance issues in addition to the very specific nature of the socio-political environment which are all factors that need to be considered in future privatisation transactions.
Keywords: Airport performance; Airport BTO agreement; BTO; Airport privatisation; Regulatory system